Introduction to AC machine design - Lipo, Thomas A. (IEEE Press series on power engineering., 2017)
AC electrical machine design is a key skill set for developing competitive electric motors and generators for applications in industry, aerospace, and defense. This book presents a thorough treatment of AC machine design, starting from basic electromagnetic principles and continuing through the various design aspects of an induction machine. Introduction to AC Machine Design includes one chapter each on the design of permanent magnet machines, synchronous machines, and thermal design. It also offers a basic treatment of the use of finite elements to compute the magnetic field within a machine without interfering with the initial comprehension of the core subject matter. Introduction to AC Machine Design brings to light more advanced principles of machine design--not just the basic principles of AC and DC machine behavior ; Introduces electrical machine design to neophytes while also being a resource for experienced designers ; Fully examines AC machine design, beginning with basic electromagnetic principles ; Covers the many facets of the induction machine design. Introduction to AC Machine Design is an important text for graduate school students studying the design of electrical machinery, and it will be of great interest to manufacturers of electrical machinery--